Adherence to a topical moisturizing preparation for regorafenib-related hand-foot skin reaction. (March 2020) - Sato, Junya; Ishikawa, Hiroshi; Hamauchi, Satoshi; Yamawaki, Yuki; Mori, Keita; Kiyohara, Yoshio; Yoshikawa, Shusuke; Yamazaki, Kentaro; Yasui, Hirofumi; Shino, Michihiro
Objective: Application of topical moisturizing preparations is important for the prevention and palliation of hand-foot skin reaction induced by multi-kinase inhibitor. Application adherence of topical moisturizing preparations in clinical practice has rarely been reported. This study investigated the factors affecting adherence to the application of topical moisturizing preparations in patients administered regorafenib. Methods: The subjects were patients administered regorafenib ( n  = 118). Consumption of a urea-based moisturizing ointment, hand-foot skin reaction grade (CTC-AE ver 3.0), treatment duration, and dose of regorafenib, factors that might affect the onset of symptoms and adherence, including age, sex, presence of a key person, working status, performance status, past use of capecitabine or epidermal growth factor receptor antibodies, and relative dose intensity were retrospectively investigated. The adherence to the topical moisturizing ointment (<21 g per week) was judged as poor. The data were analyzed by logistic regression analysis. Results: Working status was associated with poor adherence, showing a positive correlation (odds ratio; 3.024, p  = 0.023). In contrast, symptom grade of hand-foot skin reaction and regorafenib relative dose intensity showed negative correlation with poor adherence (odds ratio; 0.971, p  = 0.012, and 0.485, p  < 0.001, respectively). Conclusions: The results suggest that adherence decreases in patients with working. The relative dose intensity of regorafenib decreased when adherence to topical moisturizing ointments decreased. Severe hand-foot skin reaction could be associated with adherence. Patients consciously might not apply the ointment when hand-foot skin reaction did not become severe. It will be problematic for medical personnel to motivate patients for improving adherence to the use of moisturizing ointments.